PERENCANAAN TENAGA KERJA DI UMKM FROZEN FOOD UD ANKER CIKAMPEK - Andri Setiawan; Muhammad Wahid Hidayat; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (PT Naureen Digital Education, 2023)
This article discusses employee planning at UD frozen food SMEs. anchor. In his case, UD. Anker had a hard time dealing with perishable products. based on this, the authors found the cause of the fast perishable frozen food products, namely due to the low knowledge of proper and correct inventory management by UD employees. anchor. The business visit aims to find out the application of manpower planning and aspects that influence the manpower planning process at UD. anchor. The use of the method in this article is an observational descriptive method with an interview instrument that is given questions to the owner of the UD. Anker as a source for making articles in March 2023. The results of the interviews that have been conducted are that there are obstacles in running the UD business. Anker because of the lack of aspects in the process of implementing workforce planning in UD. anchor. The advantage in running the business is that UD. Anker can provide jobs to the surrounding community. Weaknesses in running the business are the low level of knowledge of UD employees. anchor.